Path Planning for Mobile Robots on Dynamic Environmental Obstacles Using PSO Optimization - Fahmizal Fahmizal; Innes Danarastri; Muhammad Arrofiq; Hari Maghfiroh; Henry Probo Santoso; Pinto Anugrah; Atinkut Molla (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
The increasing integration of mobile robots in various industries necessitates efficient navigation strategies amidst dynamic environments. Path planning plays a crucial role in guiding mobile robots from their starting points to target destinations, contributing to automation and enhancing human-robot collaboration. This study focuses on devising a tailored path-planning approach for a fleet of mobile robots to navigate through dynamic obstacles and reach designated trajectories efficiently. Leveraging particle swarm optimization (PSO), our methodology optimizes the path while considering real-time environmental changes. We present a simulation-based implementation of the algorithm, where each robot maintains position, velocity, cost, and personal best information to converge towards the global optimal solution. Different obstacles consist of circles, squares, rectangles, and triangles with various colors and five handle-points used. Our findings demonstrate that PSO achieves a global best cost of 5.1017, indicative of the most efficient path, minimizing overall distance traveled.